Strategy and Effectiveness of PKL Empowerment by Surakarta Government through Capabilities Regulation of the City of Surakarta Number 3 year 2008 - Beny Mukti Setiyawan, Wahyu; Wildan Khunaefi, Muhammad (Universitas PGRI Madiun, 2023)
Studies on controlling street vendors (PKL in Indonesian) as a response from a city government, might be easy to find. Even so, studies on the strategy and effectiveness of street vendor empowerment by the City Government seem to be found little. Taking the case study of the Surakarta Government with a focus on the regional regulation of the Surakarta Number 3 of 2008 as the basis for empowering street vendors, this study aims to look at the strategy and effectiveness of the empowerment of street vendors implemented by the Surakarta government through the regional regulations (PERDA in Indonesian) of Surakarta in 2008. Using the method Qualitatively using a holistic approach and the theory of capability, empowerment and participation, this study concludes that although the five street vendor empowerment strategies of the Surakarta government experience challenges in the socio-cultural, economic, legal and policy fields, it cannot be denied that the street vendor empowerment strategy in Surakarta has made good progress. Thus this study gives consideration to the Surakarta government to see the inclusive sides of street vendors in order to increase the effectiveness of empowering street vendors in Surakarta. As a final result, this study has succeeded in providing a more inclusive and sensitive framework for viewing the empowerment of street vendors through the capabilities of urban regional regulations